1993
DOI: 10.1111/j.1365-3024.1993.tb00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of eosinophils with anti‐IL‐5 antibody enhances the survival of intracranial worms of Angiostrongylus cantonensis in the mouse

Abstract: Effects of depressed eosinophilia on the development of Angiostrongylus cantonensis in the mouse were studied using monoclonal rat anti-mouse-interleukin-5 antibody (anti-IL-5). The administration of anti-IL-5 strongly depressed peripheral, cerebrospinal fluid (CSF) and medullary eosinophilic responses in mice infected with A. cantonensis, when compared with groups treated with phosphate-buffered saline solution (PBS) alone or isotype-matched rat IgG. There was no significant difference in A. cantonensis antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(56 citation statements)
references
References 20 publications
2
53
1
Order By: Relevance
“…This conclusion differs from the results of another study that demonstrated that OVA-pulsed eosinophils are capable of sensitizing mice when injected repeatedly into the peritoneal cavity (12). As eosinophils are associated with helminth parasites at the initial stage of infection (8,10,15,23), it is possible that these cells capture antigens from the helminths, migrate to T-cell-rich regions, and present antigens to T cells to initiate antigen-specific T-cell responses. Therefore, the present study also examined the ability of antigen-exposed eosinophils to prime the naïve T cells.…”
Section: Discussioncontrasting
confidence: 56%
“…This conclusion differs from the results of another study that demonstrated that OVA-pulsed eosinophils are capable of sensitizing mice when injected repeatedly into the peritoneal cavity (12). As eosinophils are associated with helminth parasites at the initial stage of infection (8,10,15,23), it is possible that these cells capture antigens from the helminths, migrate to T-cell-rich regions, and present antigens to T cells to initiate antigen-specific T-cell responses. Therefore, the present study also examined the ability of antigen-exposed eosinophils to prime the naïve T cells.…”
Section: Discussioncontrasting
confidence: 56%
“…These findings confirm previous reports in which elimination of IL-5 by mAb treatment (TRFK-5) was shown to abrogate S. stercoralis larval killing in immunized BALB/cByJ mice (18). In contrast, many other groups have found no role for IL-5 in protection from other parasites, however measurable levels of eosinophils could still be found in the peripheral blood, cutaneous tissues, cerebrospinal fluid, liver, and lungs of TRFK-5-treated mice (12,35,(37)(38)(39)(40)(41)(42)(43). Thus, the eosinophils still present in mouse tissues after mAb treatments might still have been able to mediate systemic L3 destruction.…”
Section: Discussionmentioning
confidence: 99%
“…The function of eosinophils has been studied by modulating their numbers by manipulating interleukin-5 levels (5) (13) or depleting them selectively with a monoclonal antibody against the eotaxin receptor CCR3 (8). Eosinophilia correlates with improved host protection in Angiostrongylus cantonensis (19), Strongyloides ratti (17), Strongyloides stercoralis (12), Onchocerca volvulus (14), and Litomosoides sigmodontis (15) infections. In contrast, the depletion of eosinophils did not alter the course of Schistosoma mansoni (20), Mesocestoides corti (13), and Trichuris muris (3) infections.…”
mentioning
confidence: 99%